1987
DOI: 10.1007/bf00310091
|View full text |Cite
|
Sign up to set email alerts
|

Isomyosin expression in developing chicken atria: a marker for the development of conductive tissue?

Abstract: Isomyosin expression patterns in embryonic chicken atria during the first two weeks of development were analyzed immunohistochemically. In the 3-days embryonic chicken heart (HH19-20), strong coexpression of both isomyosins can be found as band-like zones at the lateral sides of the sinoatrial junction. The zones converge on the bottom of the atrium and continue as a band around the atrioventricular canal. In the 5-days heart (HH27-28) the coexpression area encompasses the entire sinoatrial junction and extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…Because we examin ed mechan ical rather than electrical events, we cannot determine whether this effect resulted from mor e rapid electrical conduction or from differential changes in electrom echanical coupling. Although controversy remains as to whether the bundl e branches and distal Purkinje cells arise in situ in the ventricles or whether the bund le of His extends from its origin in the septum primum to produce the Purkinje network (13)(14)(15), there is no evidence of Purk inke cell precursors in the ventricle at stages as early as were examined in this study. Synchronous contra ction should be more effective than more peristaltic contraction, but only if there is atrioventricular valve competence.…”
Section: Resultsmentioning
confidence: 82%
“…Because we examin ed mechan ical rather than electrical events, we cannot determine whether this effect resulted from mor e rapid electrical conduction or from differential changes in electrom echanical coupling. Although controversy remains as to whether the bundl e branches and distal Purkinje cells arise in situ in the ventricles or whether the bund le of His extends from its origin in the septum primum to produce the Purkinje network (13)(14)(15), there is no evidence of Purk inke cell precursors in the ventricle at stages as early as were examined in this study. Synchronous contra ction should be more effective than more peristaltic contraction, but only if there is atrioventricular valve competence.…”
Section: Resultsmentioning
confidence: 82%
“…After the recordings, the isolated control or experimental hearts were photographed, fixed in Dent's fixative (80% methanol/20% DMSO), processed into paraffin, and serially sectioned at 8 m for immunohistochemical detection of early markers of ventricular conduction system (PSA-NCAM, clone 5A5, fresh ascites fluid, from Developmental Studies Hybridoma bank 15 and ␣-myosin heavy chain, clone 169-1A6, 16 shown to stain developing ventricular conduction system in the avian heart in a manner described by Sanders et al 17 Imaging was carried out on Leica TCS SP2 AOBS confocal microscope.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Monoclonal primary antibodies against human ␣MyHC (Wessels et al, 1991), human ␤MyHC (Wessels et al, 1991), chicken ␣MyHC (De Groot et al, 1987), and chicken ␤MyHC (De Groot et al, 1987), and polyclonal primary antibody against all MyHC isoforms (L53) were used. The L53 polyclonal antibody was generated as described by Sanders et al (1984) and its specificity was characterised by Western blot analysis.…”
Section: Protein Immunohistochemistrymentioning
confidence: 99%